ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP PEMAHAMAN KONSEP FISIKA SISWA - Hotmarlina Purba; Eka Ginting; Marnatauli Barasa; Mariati Simanjuntak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
In physics education, conceptual understanding is crucial because it helps students grasp the relationships between concepts, formulas, and natural phenomena as a whole. Complex physics concepts and a lack of variety in teaching materials often make it difficult for students to grasp the material. The purpose of this study is to examine how teachers use teaching materials to influence students’ understanding of physics at a private high school in Medan. The study employs a qualitative descriptive approach supported by simple quantitative data. The research subjects consisted of 25 students and one physics teacher. Data were collected through classroom observations, interviews with the teacher, and a questionnaire distributed to students. Observation and interview data were analyzed qualitatively through reduction, presentation, and drawing of conclusions, while questionnaire data were analyzed using percentages. The results of the study indicate that the use of instructional media in physics instruction is not yet ideal because lecture-based methods are still dominated by PowerPoint and the blackboard. Questionnaire results show that 96 percent of students have difficulty understanding abstract physics concepts, 92 percent have difficulty connecting concepts to daily life, and 100 percent of students say that instructional media make learning easier. Interview results indicate that simulations, laboratory experiments, and educational videos can enhance students’ understanding of concepts and their interest in learning. Limited class time and school facilities are the main constraints. This study found that improvements in students’ understanding of physics concepts are significantly influenced by the use of various types of instructional media.